SMART DOOR KEY OTOMATIS DENGAN SENSOR RFID MENGGUNAKAN MIKROKONTROLER ARDUINO UNO - Shelma Dean Aretha; Alief Aliya Rachmah; Baqiatus Sholikhah; Rafi Naura Afifah; Denny Oktavina Radianto (Universitas Pahlawan Tuanku Tambusai, 2024)
The use of innovative technology, the need for effectiveness and efficiency is prioritized in various fields. Smart door lock is a new technology for using doors automatically. From this, a new innovation was created with technological developments where the microcontroller was made more complex by using cards according to scheduling. The method used in this research is the experimental method and prototype method. After assembling each component and programming the system so that the RFID system is realized, it is necessary to test the series of components that are ready. The way this prototype system works is included in a closed system because it provides feedback on the output produced. The work of this system starts from the RFID sensor which will identify the card by taking data from the RFID number on the card. The card used will be registered in the programming system so that only registered cards can be processed by the system. When the card is attached to the RFID sensor, the RFID sensor will process the card as input and then control it using the Arduino Uno microcontroller. Then the output from this system is movement on the servo which can be applied to the door lock.